2021
DOI: 10.3390/app11156683
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Virtual Reality Applications for the Treatment of Post-Traumatic Stress Disorder

Abstract: Virtual reality (VR) technologies allow for the creation of 3D environments that can be exploited at the human level, maximizing humans’ use of perceptual skills through their sensory channels, and enabling them to actively influence the course of events that take place in the virtual environment (VE). As such, they constitute a significant asset in the treatment of post-traumatic stress disorder (PTSD) via exposure therapy. In this article, we review the VR tools that have been developed to date for the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…However, most studies still have the problem of insufficient interactivity, overemphasizing sensory stimulation, and ignoring the importance of interaction. Therefore, virtual reality exposure therapy (VRET) should apply active learning methods and increase interactive experiences [20]. Next, the analysis of patents regarding VR and counseling services are reviewed to describe the future trends of psychological therapy.…”
Section: Immersive Technology Applied As a Psychological Treatmentmentioning
confidence: 99%
“…However, most studies still have the problem of insufficient interactivity, overemphasizing sensory stimulation, and ignoring the importance of interaction. Therefore, virtual reality exposure therapy (VRET) should apply active learning methods and increase interactive experiences [20]. Next, the analysis of patents regarding VR and counseling services are reviewed to describe the future trends of psychological therapy.…”
Section: Immersive Technology Applied As a Psychological Treatmentmentioning
confidence: 99%
“…As the literature suggests, forming a "coherent memory" (Bailenson, 2018) of trauma can diminish its power, and VR is the tool that can most successfully represent trauma's complexity in an interactive and impactful way. Review studies have shown that the lack of interactivity in sensory simulation does not contribute to the active experience of the immersed subject, which is crucial for the healing effect of the experience (Kamkuimo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%